2015
DOI: 10.1016/j.bbalip.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Robust inhibitory effects of conjugated linolenic acids on a cyclooxygenase-related linoleate 10S-dioxygenase: Comparison with COX-1 and COX-2

Abstract: There are many reports of the anti-inflammatory, anti-cancer, and anti-atherosclerotic activities of conjugated linolenic acids (cLNA). They constitute a small percentage of fatty acids in the typical human diet, although up to 80% of the fatty acids in certain fruits such as pomegranate. In the course of studying a bacterial fatty acid dioxygenase (Nostoc linoleate 10S-DOX, an ancient relative of mammalian cyclooxygenases), we detected strong inhibitory activity in a commercial sample of linoleic acid. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Conjugated fatty acids exert many highly beneficial effects, including reduction of adiposity, improved insulin sensitivity, reduced carcinogenesis, and reduced atherosclerosis (reviewed in [ 170 ]). CLAs and CLnAs act via PPAR-γ (reviewed in [ 171 ]), PPAR-α [ 172 ], and inhibition of cyclooxygenases and lipoxygenases [ 173 , 174 ]. Whether typical intestinal microbiota generate sufficient CLA/CLnA to exert the extraintestinal effects seen with CLA/CLnA supplementation is unclear, as feeding essential fatty acids increases gut but not circulating levels of CLAs and CLnAs [ 164 ].…”
Section: Essential Fatty Acid-derived Metabolitesmentioning
confidence: 99%
“…Conjugated fatty acids exert many highly beneficial effects, including reduction of adiposity, improved insulin sensitivity, reduced carcinogenesis, and reduced atherosclerosis (reviewed in [ 170 ]). CLAs and CLnAs act via PPAR-γ (reviewed in [ 171 ]), PPAR-α [ 172 ], and inhibition of cyclooxygenases and lipoxygenases [ 173 , 174 ]. Whether typical intestinal microbiota generate sufficient CLA/CLnA to exert the extraintestinal effects seen with CLA/CLnA supplementation is unclear, as feeding essential fatty acids increases gut but not circulating levels of CLAs and CLnAs [ 164 ].…”
Section: Essential Fatty Acid-derived Metabolitesmentioning
confidence: 99%
“…There is an evidence that the conjugated linolenic acids exhibit potent anti-inflammatory activity, which results both from a decrease in AA transformation and the inhibition of pro-inflammatory cytokines such as TNF-α, or IL-6 [ 32 ]. Mashhadi et al [ 33 ] showed the reduction in the PGE 2 level as a result of CLnA treatment. Those authors proved that the above-mentioned dependence is related to the inhibition of both COX-1 and COX-2.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of the α-eleostearic and punicic acids was performed by using the Semi-Preparative System. The confirmation of these components was conducted by High-Performance Liquid Chromatography (HPLC), when coupled with a mass spectrometer [8]. The cell viabilities were executed with the CLNAs that were isolated from the BSO and PSO seeds, at different concentrations and with a 24 hours exposure.…”
Section: Methods and Proceduresmentioning
confidence: 99%